ANALISIS PRAKTIK GREEN SUPPLY CHAIN UMKM CIKARANG - Safitri, Wiji; Baldah, Nasrun (Jurnal Manajemen, 2024)
MSMEs are the supporting pillars of the economy. MSMEs also have an obligation to protect the environment. With this role and impact, an analysis is needed regarding the role of MSMEs in Green Supply Chain practices that seek to reduce negative impacts on the environment. The purpose of this research is to find out how to implement the Cikarang MSME Green Supply Chain practices. In practice, Green Supply Chain includes the policies, practices and tools that organizations implement in the context of a sustainable environment. This research is descriptive research that describes how the Cikarang MSMEs Green Supply Chain practices. The sample were 100 Cikarang Manufacturing MSMEs. Data was collected by distributing questionnaires using the Google form. The scale in this study is a Likert Scale 1-5. Data processing is done with Ms.Excel. The results of the study state that Cikarang MSMEs agree to carry out Green Supply Chain Practices in their business processes which consist of environmentally friendly purchasing, customer cooperation with environmental requirements, investment selection, and environmentally friendly design. By conducting this research, increasing the awareness of MSMEs to carry out business practices by reducing the negative impact on the environment.